Centrifugal Field Guided Dual Templating Synthesis of Functional Macro‐Microporous Carbon. (10th September 2018) - Ge, Qiong; Chen, Mengdi; Lou, Xiaobing; Zhang, Wei; Shen, Ming; Yang, Qi; Hu, Bingwen
Abstract: Due to the important role of porous carbon in the development of sustainable materials, the synthesis of porous carbon materials with various pore structures and pore sizes is intensively developed. But it is still not an easy task to obtain uniform porous structures at different nanoscales, let alone the hierarchical structures which combine different uniform porosity. The objective of this paper is to investigate if centrifugal field is applicable in the synthesis of ordered macro‐microporous carbon structures and the performance of the obtained porous carbon used as the cathode of a lithium–oxygen cell. It is found that a centrifugal force can trap the nucleation and growth of ZIF‐8 nanocrystals in between the interstices of close‐packed polymeric spheres, and therefore result in ordered macro‐microporous carbon nanoparticles with smaller pores distributed in the wall of larger pores. The dual porosity structures significantly help the macro‐microporous carbon to deliver a much higher capacity when used as the cathodes of a lithium–oxygen battery. Abstract : A centrifugal field assists the classical templating strategy to create a dual‐porosity . A centrifugal force traps the nucleation and growth of Zeolitic imidazolate framework‐8 nanocrystals in between polymeric spheres assembled structures, resulting in ordered macro‐microporous carbon materials. The dual porosity structure is a promising candidate for the cathodes of a lithium–oxygen cell.